ANALISIS BIBLIOMETRIK: PENINGKATAN KAPASITAS PEMERINTAH DESA DALAM PENERAPAN E-GOVERNMENT DI INDONESIA - Lutfi, Muhammad; Serlina, Andi; Nursaifullah, Nursaifullah; Hikmatun, Septi; Rasmalasani, Kiki (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2025)
Abstract This research analyzes the capacity building of village governments in Indonesia in implementing e-government. Through an in-depth literature review, this research identifies three main challenges: limitations in infrastructure, human resources, and finances. The results of the bibliometric analysis indicate an increase in research interest in this topic in recent years, highlighting the lack of studies conducted. The research results indicate that there is still a gap in understanding the factors influencing the success of e-government implementation at the village level. This research suggests the need for a comprehensive approach to address these challenges, including increased investment in information technology infrastructure, the development of structured training programs for village officials, and the provision of sustainable financial support.